Analysis of Heritability Across the Clinical Phenotypes of Frontotemporal Dementia and the Frequency of the C9ORF72 in a Colombian Population - López-Cáceres, Andrea; Velasco-Rueda, María; Garcia-Cifuentes, Elkin; Zarante, Ignacio; Matallana, Diana (Frontiers in Neurology, 2021)
Frontotemporal dementia (FTD) is a highly heritable condition. Up to 40% of FTD is familial and an estimated 15% to 40% is due to single-gene mutations. It has been estimated that the G4C2 hexanucleotide repeat expansions in the C9ORF72 gene can explain up to 37.5% of the familial cases of FTD, especially in populations of Caucasian origin. The purpose of this paper is to evaluate hereditary risk across the clinical phenotypes of FTD and the frequency of the G4C2 expansion in a Colombian cohort diagnosed with FTD. Methods: A total of 132 FTD patients were diagnosed according to established criteria in the behavioral variant FTD, logopenic variant PPA, non-fluent agrammatic PPA, and semantic variant PPA. Hereditary risk across the clinical phenotypes was established in four categories that indicate the pathogenic relationship of the mutation: high, medium, low, and apparently sporadic, based on those proposed by Wood and collaborators. All subjects were also examined for C9ORF72 hexanucleotide expansion (defined as >30 repetitions). Results: There were no significant differences in the demographic characteristics of the patients between the clinical phenotypes of FTD. The higher rate phenotype was bvFTD (62.12%). In accordance with the risk classification, we found that 72 (54.4%) complied with the criteria for the sporadic cases; for the familial cases, 23 (17.4%) fulfilled the high-risk criteria, 23 (17.4%) fulfilled the low risk criteria, and 14 (10.6%) fulfilled the criteria to be classified as subject to medium risk. C9ORF72 expansion frequency was 0.76% (1/132). Conclusion: The FTD heritability presented in this research was very similar to the results reported in the literature. The C9ORF72 expansion frequency was low. Colombia is a triethnic country, with a high frequency of genetic Amerindian markers; this shows consistency with the present results of a low repetition frequency. This study provides an initial report of the frequency for the hexanucleotide repeat expansions in C9ORF72 in patients with FTD in a Colombian population and paves the way for further study of the possible genetic causes of FTD in Colombia.